THE INFLUENCE OF ISLAMIC SPIRITUAL EXTRACURRICULAR ON THE MORALS OF STUDENTS - Munawaroh, Nenden; Fadilah, Elsa; Nasrullah, Yufi M; Usman, Asep Tutun (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2022)
The background of this study is the existence of technology that affects the nature, morals, and character of learners, for example, characterized by learners who communicate with teachers using non-formal languages, female learners who wear clothes follow trends so as not to close their aurat perfectly, learning hours 8-9 hours per day make moral education only focused on the school environment. This study aims to find out the extracurricular influence of Islamic Spiritual on the morals of students at SMAN 15 Garut. The research uses quantitative approaches and descriptive methods. The subject of this study is a student who follows Islamic spiritual extracurriculars at SMAN 15 Garut. The object of this research is the result of the influence of the Islamic Spiritual in forming student morals. This researched data collection uses observations, interviews, and documentation. Data analysis techniques use quantitative techniques. In this study, obtaining data with variable calculation X resulted in reliability and validity with a total variant of 11,375, variant items of 129,387, tcount of 20.81, and ttable of 2.01 in a Reliable decision. Calculating variable Y with a total variant of 53.53, variant items of 7.32, t-count of 16.10, and t-table of 2.01 with Realiabel decision. After the hypothesis test produced t-count data of 8.66 and a t-table of 2.01, it can be concluded that the hypothesis Ho was rejected and Ha accepted, with a determination influence of 45% with an epsilon of 55% and including medium criteria. So it can be concluded that ROHIS extracurriculars affect the morals of students at SMAN 15 Garut by 45%.